Relationship between tumour-associated macrophages, CD8+ and IL17+ Cells, TGF-β, TGF-βRII, IL-17R and WNT signaling in colorectal carcinoma - Chai, Boon Yean (2018)
Colorectal carcinoma is one of the most common cancers and is a heterogeneous disease. The inflammatory tumour microenvironment plays a critical role in colorectal carcinoma development. Many researchers have extensively studied tumour-associated macrophages (TAMs), CD8+ cells, IL-17+ cells, TGF-β and IL-17 expressions as well as Wnt signaling in the tumour microenvironment of colorectal carcinoma. However the relationship between TAMs, CD8+ cells, IL-17+ cells, expression of TGF-β and IL-17 receptors and ligands and Wnt signaling are poorly understood. The main objective of this study is to study interrelationship of M1 TAMs and M2 TAMs with CD8+ cells, IL-17+ cells TGF-βRII, TGF-β, IL-17R, IL-17, and biomolecules of Wnt signaling in the progression of colorectal carcinoma. Double immunohistochemical staining was performed to evaluate densities of CD68+/iNOS M1 TAMs and CD68+/CD163+ M2 TAMs in colorectal carcinoma. Single immunohistochemical staining was performed to determine the density of CD8+ cell and IL-17+ cells and expression of TGF-β and IL-17 receptors and ligands. Using Spearman's correlation, a positive correlation were observed between CD8+ T cells and IL-17+ cells (p=0.031); M1 TAMs and TGF-βRII expression (p<0.001); M1 TAMs and IL-17 expression (p=0.003); IL-17+ cells and IL-17 expression (p=0.031); TGF-βRII expression and IL-17R expression (p=0.011); M2 TAMs and loss of nucleus APC (p=0.013); M2 TAMs and loss of cytoplasmic APC (p=0.011); M1/M2 and loss of cytoplasmic APC (p=0.001); M1 TAMs and p- GSK3β (p=0.003); IL-17+ cells and p-GSK3β (p=0.014); TGF-βRII expression and p-GSK3β (p=0.020). A negative correlation were found between M1 TAMs and CD8+ T cells/IL-17+ cells (p=0.007); M2 TAMs and TGF-β expression (p=0.0007); M2 TAMs and TGF-βRII expression (p=0.049); M1/M2 and TGF-β expression (p=0.031); M1/M2 and TGF-βRII expression (p=0.001). Densities of immune cells and biomolecules in this study were associated with various demographical and clinicopathological features using chi-square test. Early TMN stage was associated with high density of M2 TAMs (p<0.001) and IL- 17+ cells (p<0.001), low CD8+ T cell/IL-17+ cells (p<0.001), high expression of TGF-βRII (p<0.001) and IL-17R (p=0.027). Low histological grade of tumour was associated with high density of IL-17+ cells (p=0.035), high expression of IL-17R (p=0.019) and low CD8+ cell/IL-17+ cells (p=0.030). Decreased depth of tumour invasion (T) was associated with high density of IL-17+ cells (<0.001) and IL-17R (p=0.023). Low lymph nodes metastasis (N) was associated with high density of M2 TAMs (p=0.005) and IL-17+ cells (p<0.001). In conclusion, this study demonstrated that high density of M2 TAMs and IL-17+ cells, high expression of TGF-βRII and IL-17R, and low CD8+ cells/IL-17+ cells are associated with early TNM stage, low histological grade, decreased depth of tumour invasion, low lymph nodes metastasis indicating a favourable prognosis of colorectal carcinoma. M1 TAMs and IL-17 expression are positively correlated TGF-βRII and IL-17+ cells respectively. This implied high density of M1 TAMs and high IL-17 expression also indicating a favourable prognosis. Hence, evaluation of immune cells, ligands and receptors of cytokines may serve as a potential biomarker for assessing colorectal carcinoma progression and developing immune cells/cytokine targeted treatment.